Compression behaviour of concrete cylinder with Carbon Fibre Reinforced Polymer (CFRP) confinement / Norsalwa Aisyah ... [et al.] - Norsalwa Aisyah; Senu Ruqayyah; Wahid, Ismail Norlizan; Ahmad, Hazrina; Ahmad Zakwan, Fariz Aswan (UiTM Press for the Research Management Center (IRMI), Universiti Teknologi MARA, 2021)
Carbon fibre reinforced polymer (CFRP) confinement has always been one of the strengthening methods available for a vulnerable concrete column. This paper presents the compressive behaviour of nine circular concrete cylinders with CFRP confinement. Three different specimen conditions considered; full CFRP confinement, partial CFRP confinement, and unconfined (control specimen). Nine concrete cylinders with lOO mm x 200 mm were tested under compression load. It is discovered that full and partial CFRP confinement had improved concrete cylinder ultimate load capacity by 3OO% and l5O% respectively when compared to the unconfined concrete cylinder. With 150% strength enhancement achieved by partial CFRP confined specimen, it is proven that partial CFRP confinement does provide sufficient confinement in enhancing concrete column strength as full CFRP confinement. This finding has led to remarkable discoveries which with lesser CFRP used the functionality of CFRP as strengthening material can still be utilized. Therefore, could contribute significant input to the construction industry in using lesser CFRP for more sustainable material approach.